Resistência a fungicidas estrobilurinas em populações de Pyricularia oryzae de áreas de trigo no Brasil - Oliveira, Samanta Cristiene de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Wheat blast disease caused by Pyricularia oryzae is the most important across central- southern Brazil. Its control has relied strongly on strobilurin fungicides (Quinone oxidase inhibitors, QoI). Resistance to QoI (QoI-R) has been reported for several pathosystems worldwide. In this study we tested the hypothesis that the main Brazilian populations of P. oryzae associated with wheat remain sensitive to QoI fungicides. In contrast, the alternative hypothesis that extensive and consecutive use of QoI fungicides in the last two decades for the management of wheat blast in the Center-South region of Brazil was tested, led to the emergence and widespread distribution QoI-R in populations P. oryzae associated with the wheat in the main growing areas of the country. It is determined also whether other species of grasses adjacent fields of wheat plants housed QoI R-populations of P. oryzae, serving as a resistant pathogen inoculum reservoir. The main objectives were to study the occurrence and distribution of resistance to QoI fungicides in P. oryzae populations associated with wheat and other species of plants grasses adjacent to wheat fields in South-Central Brazil, examining mutations in the cytochrome b gene (cyt b) and determining the sensitivity of the isolates of P. oryzae azoxystrobin in vitro experiments. In this study, we report the widespread distribution of QoI-R in populations of P. oryzae from Brazilian wheat fields of 325 isolates, of which 198 derived from wheat fields and 91 from weeds within wheat fields sampled in 2012, and 36 from wheat sampled in 2005. Sequencing of cytB gene distinguished nine haplotypes, two of which shared between wheat and weeds-derived isolates, and seven exclusive to weed isolates. Four of these haplotypes had the G143A mutation associated with resistance to QoI (QoI-R). While 90% of the wheat isolates of P. oryzae and 48% of the weed-derived ones sampled in 2012 ...

A brusone, causada por Pyricularia oryzae, é a doença mais importante do trigo em todo Centro-Sul do Brasil. Seu controle tem dependido, fortemente do uso de fungicidas estrobilurinas, inibidores de quinona oxidase, QoI. Resistência aos fungicidas QoI (QoI-R) já foram constatadas para diversos patossistemas em todo o mundo. Neste trabalho testou-se a hipótese principal de que as populações brasileiras de P. oryzae associadas com o trigo permanecem sensíveis aos fungicidas QoI. Em contraste, foi testada a hipótese alternativa de que o uso extensivo e consecutivo de fungicidas QoI nas duas últimas décadas para o manejo da brusone do trigo na região Centro-Sul do Brasil, levou à emergência e a distribuição generalizada de QoI-R em populações de P. oryzae associadas ao trigo nas principais áreas de cultivo do país. Determinou-se, também, se outras espécies de plantas poáceas adjacentes a campos de trigo hospedavam populações QoI-R de P. oryzae, servindo como um reservatório de inóculo do patógeno resistente. Os principais objetivos foram estudar a ocorrência e a distribuição da resistência aos fungicidas QoI em populações de P. oryzae associadas ao trigo e a outras espécies de plantas poáceas adjacentes a campos de trigo no Centro-Sul do Brasil, examinando as mutações no gene citocromo b (cyt b) e determinando a sensibilidade dos isolados de P. oryzae a azoxistrobina em experimentos in vitro. Foi analisada a distribuição generalizada de QoI-R em populações de P. oryzae em campos brasileiros de trigo de 325 isolados, dos quais 198 foram derivados de trigo e 91 de outras plantas poáceas amostradas nos mesmos campos de trigo, em 2012, e 36 isolados de trigo obtidos em 2005. O sequênciamento do gene cyt b distinguiu nove haplótipos, dois compartilhados entre trigo e outras plantas poáceas e sete exclusivos de outras plantas poáceas. Quatro desses haplótipos...
Keywords: Melhoramento genetico; Trigo - Doenças e pragas; Brusone; Fungicidas; Genetica vegetal; Breeding